STAT1/2 is involved in the inhibition of cell growth induced by U0126 in Hela cells - Zhao, L Y; Huang, C; Li, Z F; Liu, L; Ni, L; Song, T S (Cellular and Molecular Biology, 2009)
The mitogen-activated protein kinase (MAPK) signaling cascade plays an important role in cell life. Herein we show that small interfering RNAs targeting MAPK1 can inhibit HeLa cell growth and induce apoptosis along with up-regulation of signal transducers and activator 1 and 2 (STAT1/2). However, across-talk between the ras-raf-ERK1/2 signalling cascade and the JAK-STAT pathway remain largely unknown. Using MEK inhibitor U0126 and JAK-2 inhibitor AG490, we analyzed the relationship between ERK1/2 and STAT1/2 in HeLa cells. U0126 inhibited HeLa cell growth, arrested the cell cycle at G1/G0, and induced cell apoptosis, and AG490 partially reversed the effects of U0126. U0126 induced up-regulation of ERK1/2 and down-regulation of phosphorylated ERK1/2, increased STAT1 and STAT2 expression in a dose-dependent manner, and activated STAT1/2 via their phosphorylation. AG490 markedly inhibited the phosphorylation of STAT1 and STAT2 and slightly increased that of ERK1/2 inhibited by U0126. We suggest that STAT1/2 is involved in the inhibition of cell growth induced by U0126 in HeLa cells.